Long Noncoding RNA UCA1 Is Related to Autophagy and Apoptosis in Endometrial Stromal Cells - Jiang, Lili; Wan, Yahui; Feng, Ziyi; Liu, Da; Ouyang, Ling; Li, Yan; Liu, Kuiran (Frontiers in Oncology, 2021)
Research question Long non-coding RNA (LncRNA) urothelial carcinoma-associated 1(UCA1) in embryonic tissues are higher than those in most cancer tissues such as bladder cancer, which indicates that RNA is a carcinoembryonic antigen. However, there are no published reports on the role of UCA1 in endometriosis (EMs). Therefore, to address this gap of knowledge, we decided to assess the potential role of lncRNA UCA1 in the pathogenesis and progression of EMs. Design In order to ratify the expression of UCA1 in EMs,quantitative reverse transcription polymerase chain reaction (qRT-PCR) was used. RNA interference (siRNA) was used to study the biological function of UCA1 in EMs in vitro. Results qRT-PCR showed that the expression of lncRNA UCA1 in EMs was higher (P <0.01).In vitro, knockdown of UCA1 could significantly inhibit the proliferation of endometriosis stromal cells (ESCs) and induce their autophagy and apoptosis. Conclusion UCA1 is highly expressed in EMs and promotes the proliferation of ESCs, but suppresses autophagy and apoptosis. In EMs，UCA1 is prospected to become a prognostic marker and therapeutic target.